Departure Stories : Betty Crocker Made Matzoh Balls (and other lies) - Bernick, Elisa (Book collections on Project MUSE., 2022)
""We weren't religious per se. The most frequent mention of God in our house was my mother yelling 'Goddammit!'" Elisa Bernick grew up "different" (i.e., Jewish) in the white, Christian suburb of New Hope, Minnesota during the 1960s and early 1970s. At the center of her world was her mother, Arlene, who was a foul-mouthed, red-headed, suburban Samson who ultimately shook the walls of their family until it collapsed. Poignant and provocative, Departure Stories peers through the broader lens of Minnesota's recent history to reveal an intergenerational journey through trauma that unraveled the Bernick family and many others. Deftly interweaving reporting, archival material, memoir, jokes, scrapbook fragments, personal commentary, and one very special Waikiki Meatballs recipe, Bernick explores how the invisible baggage of place and memory, Minnesota's uniquely antisemitic history, and the cultural shifts of feminism and changing marital expectations contributed to her family's eventual implosion. Departure Stories: Betty Crocker Made Matzoh Balls (and other lies) is a personal exploration of erasure, immigrants, and exiles that examines the ways departures-from places, families and memory-have far-reaching effects"--